Pengaruh Kualitas Layanan Terhadap Kepuasan Peserta Asuransi Syariah (Studi Kasus Peserta Dana Pendidikan Pada PT. Sun Life Financial Syariah Cabang Kota Medan) - Zulfitri, Zulfitri; Syahriza, Rahmi (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Educational insurance is a combined product of life insurance plus money market instruments. Insurance will guarantee the cost of a child's education if later parents can no longer earn a living due to death, or total disability.  education at PT Prudential Pruaini Medan City Branch.  The tennis of this research is descriptive quantitative where the researcher conducts self-observation or WACNA with the structure using a notebook. The results of the study indicate that there are factors that influence the request for education insurance at PT Prudential Pruaini Medan City Branch.  The Prudential Pruaini Medan City Branch is the income factor of the Lysia factor.